Revisiting finite difference and finite element methods applied to structural mechanics within enriched continua - Challamel, Noël; Picandet, Vincent; Collet, Bernard; Michelitsch, Thomas; Elishakoff, Isaac; Wang, C.M. (European journal of mechanics, A, Solids, 2015)
In this paper, we revisit the capability of numerical approaches such as finite difference methods and finite element methods, in approximating exact one-dimensional continuous eigenvalue problems (such as lateral vibrations of a string, the axial or the torsional vibrations of a bar, and the buckling of elastic columns). The numerical methods analysed in this paper are converted into difference equations. Following a continualization procedure or the method of differential approximation, the difference operators are then expanded in differential operators via Taylor expansion or Padé approximants. Analogies between the finite numerical approaches and some equivalent enriched continuum are shown, using this continualization procedure. The finite difference methods (first-order or higher-order finite difference methods) are shown to behave as integral-based nonlocal media (or stress gradient media), while the finite element method is found to behave as gradient elasticity media (or strain gradient media). The length scale identification of each equivalent enriched continuum strongly depends on the order of the numerical method considered. For the finite difference methods, the length scale identification of the equivalent nonlocal medium depends on the static versus dynamic analysis, whereas this length scale appears to be independent of inertia effects for the finite element method. Some comparisons between the exact discrete eigenvalue problems and the approximated continuous ones show the efficiency of the continualization procedure. An equivalent enriched Rayleigh quotient can be defined for each numerical method: the integral-based nonlocal method gives a lower bound solution to the exact eigenvalue multiplier, whereas the gradient elasticity method furnishes an upper bound solution. •Finite difference method and finite element method are revisited within enriched continua.•The finite equations are continualized using the method of differential approximation.•One dimensional eigenvalue problems (buckling and vibrations problems) are considered.•Both numerical methods can be approximated by some nonlocal or gradient elasticity constitutive laws.•Higher-order finite difference scheme can be formulated into a higher-order nonlocal law.•The convergence rate of the finite numerical approaches is quantified using the associated enriched Rayleigh's quotient.